1976
DOI: 10.19182/remvt.8037
|View full text |Cite
|
Sign up to set email alerts
|

Ecologie de Glossina palpalis gambiensis Vanderplank, 1949

Abstract: L'auteur passe en revue les différents points de l'écologie de Glossina palpalis étudiés en Afrique occidentale: répartition des sous-espèces, environnement, action des facteurs écologiques sur l'imago et la pupe, comportement (activité et lieux de repos), relations avec les autres animaux, dispersion et dynamique des populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…G. palpalis gambiensis lives in forests where optimal atmospheric conditions can be maintained (Challier, 1973). These forests include the gallery forests along the Black Volta River.…”
Section: Discussionmentioning
confidence: 99%
“…G. palpalis gambiensis lives in forests where optimal atmospheric conditions can be maintained (Challier, 1973). These forests include the gallery forests along the Black Volta River.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersal of G. tachinoides may be less influenced by landscape fragmentation because it is more xerophylous. Indeed, previous studies have shown that G. tachinoides tolerates a drier environment than does G. p. gambiensis; the optima for G. p. gambiensis are a temperature of 23-26 • C and a relative humidity (RH) of 70-81%, whereas optimum conditions for G. tachinoides are 28-32 • C and 55-75% RH (Challier, 1973;Rogers, 1979). Typical habitat for G. tachinoides corresponds to open riparian vegetation, where shrubs predominate, whereas G. p. gambiensis needs closed gallery forests (Bouyer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…All tsetse catches were recorded, separated into males and females. The physiological age of males was determined through wing fray analysis [6].…”
Section: Methodsmentioning
confidence: 99%